Differences in Clinicopathological Characteristics of Papillary Thyroid Carcinoma between Symptomatic and Asymptomatic Patients with Primary Hyperparathyroidism - Yuan Liu; Siyi Guo; Shaowei Sang; Jinbo Liu; Lin Qi; Bin Lv; Xiaoli Zhang (International Journal of Endocrinology)
Background. Popularization of cervical ultrasound led to higher detection of papillary thyroid carcinoma (PTC) and primary hyperparathyroidism (PHPT), as well as increasing percentage of asymptomatic PHPT in China. Although the coexistence of PTC and PHPT has been reported, it is unknown whether the clinicopathological features of PTC differ between asymptomatic and symptomatic PHPT patients. Methods. We retrospectively reviewed the medical records of 304 PHPT patients treated in our hospital between January 2009 and July 2020, including 217 females and 87 males with the average age of 53.27 ± 13.54 years. Of the 304 patients, 181 were symptomatic PHPT patients and 123 were asymptomatic PHPT patients. We analyzed the laboratory results, postoperative pathology, and the TNM stage of PTC between asymptomatic and symptomatic PHPT patients. Results. Concurrent thyroid nodules were found in 61.51% of PHPT patients, and the prevalence of PTC in thyroidectomized PHPT patients was 29.89% in our cohort. Lower serum parathyroid hormone (PTH) (p<0.05) and calcium (p<0.05) were found in PHPT patients with PTC compared to patients with benign thyroid lesion. Compared with the symptomatic PHPT patients, the asymptomatic PHPT patients showed lower serum calcium (p<0.05), serum chlorine (p<0.05), alkaline phosphatase (p<0.05), PTH (p<0.05), and bone turnover markers (p<0.05) but higher prevalence of thyroid nodules (70.73% versus 55.24%, p<0.05) and PTC (15.44% versus 3.87%, p<0.05). All the PTC in symptomatic PHPT patients were papillary microcarcinoma limited to the thyroid, while 68.42% and 15.78% of the PTC in asymptomatic PHPT patients showed microscopic extrathyroidal extension and lymph node metastases, respectively. Moreover, 36.84% (7/19) of the PTC patients in asymptomatic group showed multifocality, which was much higher than 14.29% (1/7) in the symptomatic group; however, no statistical significance was found (p=0.24). Conclusions. The concomitant PTC in asymptomatic PHPT patients showed a higher rate of microscopic extrathyroidal invasion when compared to symptomatic PHPT patients. So the FNA is essential to the asymptomatic PHPT patients with suspicious thyroid nodules and once the PTC is confirmed, concurrent parathyroidectomy should be performed with thyroidectomy in asymptomatic PHPT patients.